Effect of Multi-Walled Carbon Nanotubes on lung tissue and concentration of enzyme Carbonic anhydrase in the New Zealand white rabbit - Farah M. Ghazal; Muna H. Jankeer; Hafidh I. Al-Sadi (Tikrit Journal of Pure Science, 2023)
The aim of the present study was to investigate the effect of variable doses of Multi Carbon Nanotubes (MWCNTs) 1,3,5 mg/ml/kg body weight on lung weight and their effect on the concentration of Carbonic anhydrase(CA), morphological and histopathological changes of the males New Zealand white rabbits, In this study  was used 40 New Zealand white rabbit of males, their ages range between (12-18 months) divided into four groups, ten for each group which intratracheal instillation with Nanoparticles, At days 7 and 90 post exposure, The blood , lung and trachea tissue samples were collected for each group.